2010
DOI: 10.1111/j.1749-6632.2009.05100.x
|View full text |Cite
|
Sign up to set email alerts
|

Return to the fetal gene program

Abstract: A hallmark of cardiac metabolism before birth is the predominance of carbohydrate use for energy provision. After birth, energy substrate metabolism rapidly switches to the oxidation of fatty acids. This switch accompanies the expression of “adult” isoforms of metabolic enzymes and other proteins. However, in a variety of pathophysiologic conditions, including hypoxia, ischemia, hypertrophy, atrophy, diabetes, and hypothyroidism, the postnatal heart returns to the “fetal” gene program. These adaptive mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
212
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(218 citation statements)
references
References 47 publications
5
212
0
1
Order By: Relevance
“…Okere et al (30) also reported that a high-fat diet prevented a Mhc-␣ to Mhc-␤ isoform switch that was accompanied by reductions in LV remodeling and contractile dysfunction in hypertensioninduced hypertrophy. In addition, increased glucose availability has been reported to promote the Mhc-␣ to Mhc-␤ isoform switch, whereas high fatty acid levels blocked the changes in myosin isoforms (41,49) considered a hallmark for a progressive decline in cardiac function. Thus, there may be a metabolic link that functions to protect the heart under pathological conditions through alterations in gene and protein expression involved in regulating contractile function; however, a potential cardioprotective effect may be unique to our model of mild-moderate HF/LV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okere et al (30) also reported that a high-fat diet prevented a Mhc-␣ to Mhc-␤ isoform switch that was accompanied by reductions in LV remodeling and contractile dysfunction in hypertensioninduced hypertrophy. In addition, increased glucose availability has been reported to promote the Mhc-␣ to Mhc-␤ isoform switch, whereas high fatty acid levels blocked the changes in myosin isoforms (41,49) considered a hallmark for a progressive decline in cardiac function. Thus, there may be a metabolic link that functions to protect the heart under pathological conditions through alterations in gene and protein expression involved in regulating contractile function; however, a potential cardioprotective effect may be unique to our model of mild-moderate HF/LV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, at the myofilament level, the composition and phosphorylation of contractile proteins also impact contractility. The relative abundance of myosin heavy chain (MHC) ␣-and ␤-isoforms correlates with in vivo contractile function (41). Specifically, an increase in MHC-␤ contributes to decreased in vivo contractile function as a result of lower intrinsic ATPase activity and reduced myofilament shortening velocity (46).…”
mentioning
confidence: 99%
“…Many β-blocker-associated gene expression changes in responders versus nonresponders represent a partial reversal of the cardiac fetal/adult gene program, 3,34,35 but they may also be consistent with alternative regulatory mechanisms including inhibition of β 1 -AR signaling 5,6,36 or enhanced thyroid hormone receptor (TR-α) activity (Table 5). 7 We previously reported changes in TR-α1 and TR-α2 expression in IDC LVs consistent with hypothyroidism at the TR-α level.…”
Section: Figure 3 Continuedmentioning
confidence: 99%
“…Sarcomere reorganisation resulting in the remodelling of the cardiomyocytes, affecting the ability of the cardiomyocytes to contract (Telley et al, 2007). The activation of the "fetal gene program" involves the re-expression (in the adult) of genes normally only expressed during fetal development including of α-skeletal actin, β-myosin heavy chain (β-MHC), atrial natriuretic peptide (ANP) and myosin light chain-2v (MLC-2V) (Parker et al, 1990;Taegtmeyer et al, 2010). Some of the induced fetal genes code for contractile proteins.…”
Section: Types Of Cardiac Hypertrophymentioning
confidence: 99%
“…handling proteins potentially contributes to alterations in the contractile ability of cardiomyocytes (Razeghi et al, 2001;Taegtmeyer et al, 2010).…”
mentioning
confidence: 99%